Penggambaran Profesi Trauma Cleaner dalam Web Series â€œMove to Heavenâ€ - Altobeli Lobodally (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
South Korea has an unusual profession. The profession is a trauma cleaner profession that appears in the web series Move to Heaven. This study aims to determine the portrayal of trauma cleaner profession in the web series Move to Heaven. This study uses the theory of Social Reality construction and semiotic analysis using Charles Sanders Peirce through the Triangle meaning of sign, object, and interpretation. The results of this study found that there are nine depictions of the trauma cleaner profession that are divided into two, namely positive and negative. Among them, the trauma cleaner profession is described as a profession that is conscientious in taking care of death, has high integrity and is professional in its work, loves cleanliness and obeys regulations, requires calmness and concentration, has high empathy, has good relationships with other professions, and is a noble profession. In addition, the profession of trauma cleaner is looked down upon by the community and is prone to mental disorders. Thus, web series become a construction tool of social reality, especially regarding the profession.